Kansei evaluation of headscarf (hijab, tudung) designs - Ismail, Azkar Zahidi; Mohd Zamri, Muhamad Zul Asraf; Adnan, Ammar; Mat Hasan, Mohd Raziff; Muhamad Khairussaleh, Nor Khairusshima; Abdul Hamid, Abd. Malek (Malaysian Ministry of Higher Education, 2018)
Headscarf (tudung in Malay Language) has become one of the Muslimah fashion. Nowadays, there are massive brands and designs of tudung are available in the market. However, most of the designs are dependent on designers’ artistic sensibility. Moreover, lack of proper consideration on user preferences may results in an unfit product that may minimize the potential profit. This study used Kansei evaluation to obtain user preferences on tudung in general, more specifically, on the design criteria of the tudung in Malaysian context. Twenty-five participants were involved in a semi-structured interview, and three designs of tudung were selected (namely Ariani, Naelofar, and Galeria), and ten Kansei words were obtained (trending, beautiful, quality fabric, non-transparent, cooling effect, comfortable, easy to wear, easy to shape, wrinkle free, and uncrowded design). These information were then converted into a Kansei Questionnaire, in which a respondent was asked to rate the three selected designs based on the ten Kansei words. 158 respondents were completed the questionnaire. In overall, Ariani scored the highest among the three designs (M = 3.86; SD = 0.367), follows closely by Galeria (M = 3.85; SD = 0.321), and the lowest was Naelofar (M = 3.40; SD = 0.321). The result also reveals that there is a significant difference between the three chosen designs at p < 0.05, [F (2, 27) = 6.295, p = 0.006]. The results from this study give an additional information regarding the user preferences on tudung’s design in general, more specifically, recommends the preferable tudung design based on the design criteria, in which will optimized the fit between the design and user preferences.